KOMUNITAS ARTHROPODA PADA AGROEKOSISTEM JAGUNG MANIS DAN KACANG PANJANG DENGAN DAN TANPA PERLAKUAN INSEKTISIDA DI LAHAN GAMBUT - Melhanah, Melhanah; L, Supriati; D, Saraswati (AgriPeat, 2015)
The purpose of the study was to determine the arthropod communities treat and untreated chemical insecticides on crops of sweet corn and long bean crop in peatland, Kalampangan. The experiment was conducted in area of 210 m2 and divided into 12 experimental plots (each plot was 12 m2). Sampling and sample observations carried out at 2-8 weeks after planting. Sampling using a sweep net to arthropods which are in the crown area and pitfall traps for arthropod at ground level area. On the sweet corn and long bean crop, the results showed arthropods are more common in crop of untreated chemical insecticide than that treated insecticide. Guilds between fitofag, natural enemies of predators and parasitoids and neutral arthropod interaction has occurred